Strategi Peningkatan Komitmen SDM Dan Pengembangan Bisnis Model Canvas (BMC) Kampung Madu KTH Bina Lestari Pasca Pandemi Covid-19 - Yulia Khoerunnisa; Indah Permatasari (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research is aimed to identify, describe, and develop strategies to enhance group members' commitment in the development of a health honey business using the Business Model Canvas (BMC). The study was conducted at KTH Bina Lestari in Ciamis Regency, post the Covid-19 pandemic. Data collection was carried out through interviews, observations, and documentation. Data analysis was used to assess internal and external factors to determine the highest priority for development and improvement. The research findings indicate that the selected priority strategies for honey business development in Kampung Madu are: 1) training and human resource development, 2) product quality improvement, and 3) product marketing optimization.